Sensing marine biomolecules: smell, taste, and the evolutionary transition from aquatic to terrestrial life - Mollo, Ernesto; Fontana, Angelo; Roussis, Vassilios; Polese, Gianluca; Amodeo, Pietro; Ghiselin, Michael T. (Frontiers in Chemistry, 2014)
The usual definition of smell and taste as distance and contact forms of chemoreception, respectively, has resulted in the belief that, during the shift from aquatic to terrestrial life, odorant receptors (ORs) were selected mainly to recognize airborne hydrophobic ligands, instead of the hydrophilic molecules involved in marine remote-sensing. This post-adaptive evolutionary scenario, however, neglects the fact that marine organisms 1) produce and detect a wide range of small hydrophobic and volatile molecules, especially terpenoids, and 2) contain genes coding for ORs that are able to bind those compounds. These apparent anomalies can be resolved by adopting an alternative, pre-adaptive scenario. Before becoming airborne on land, small molecules, almost insoluble in water, already played a key role in aquatic communication, but acting in “contact” forms of olfaction that did not require major molecular innovations to become effective at a distance in air. Rather, when air was “invaded” by volatile marine terpenoids, an expansion of the spatial range of olfaction was an incidental consequence rather than an adaptation.